Technique for Integrating the Digital Coordinated Cadastral Data With Mapping Data (Module C) - Ses, Sahrum; Omar, Abdullah Hisam (2003)
To Design several experiments employing various techniques related to integration issues that can assure the quality and integrity of GIS output, To propose techniques of integrating DCDB and CAMS data in the GIS environments so that users of the data sets can obtain output for their applications.